Global status of knowledge for prevention and emergency management of traumatic dental injuries in sports persons and coaches: A systematic review. Issue 2 (5th December 2020) - Tewari, Nitesh; Johnson, Riya Marie; Mathur, Vijay Prakash; Rahul, Morankar; Goel, Shubhi; Ritwik, Priyanshi; Bansal, Kalpana; Atif, Mohammad
Abstract: Background/Aims: Sports‐related dental injuries can cause pain, disfigurement, and broken teeth which may affect the athlete's well‐being and psychological status. Such injuries may also lead to the fear of re‐injury and other problems. Since a delay in adequate emergency treatment can have adverse effects, it is imperative that athletes and coaches have sufficient awareness of emergency treatment options. Hence, the aim of this systematic review was to evaluate the global status of knowledge among athletes and coaches regarding the prevention and emergency management of traumatic dental injuries. Methods: The protocol was designed using the PRISMA guidelines and registered in PROSPERO (CRD42020184956). A broad‐based search using text words and MeSH terms was performed in established databases according to a predefined strategy without any distinction of language and year of publication. Studies without details of the questionnaire, knowledge score, validity, and reliability were excluded. Data extraction was performed and risk‐of‐bias assessment was done by means of the Joanna Briggs Institute's critical appraisal tool. Results: Nine studies published between 2005 and 2020 were included for qualitative synthesis. They were primarily from Asia with none from North America and Australia. Most of them were cross‐sectional, used convenience sampling, and were interview‐based. Less than 10% of the participants in two studies had adequate knowledge of the immediate emergency management of tooth avulsion, while only 2.4% of basketball players and coaches knew that it was necessary to collect the avulsed tooth or broken tooth fragments. The overall level of knowledge was reported as poor or insufficient in all studies, with moderate or high risk‐of‐bias in six studies. Conclusion: The knowledge regarding emergency management of TDI was found to be low globally. Along with the choice of the sport, there was a high level of variability in the study design and sampling characteristics.